Genetic variants in the calcium signaling pathway participate in the pathogenesis of colorectal cancer through the tumor microenvironment - Wu, Jing-Yu; Shao, Yu; Huang, Chang-Zhi; Wang, Zhen-Ling; Zhang, Hong-Qiang; Fu, Zan (Frontiers in Oncology, 2023)
Background Cancer risk is influenced by calcium signaling in intracellular and intercellular signaling pathways. However, the relationship between the calcium signaling pathway and colorectal cancer risk remains unknown. We aim to evaluate the role of genetic variants in calcium signaling pathway genes in colorectal cancer risk through the tumor microenvironment. Methods An analysis of genetic variants in the calcium signaling pathway was conducted using a case-control study that included 1150 colorectal cancer patients and 1342 non-cancer patients. Using the regression model, we assessed whether single-nucleotide polymorphisms (SNPs) increase the risk of colorectal cancer. We also performed a dual luciferase reporter gene assay using HCT116 cell lines and DLD1 cell lines to demonstrate the regulatory relationship between SNP and candidate risk gene. We evaluated the expression of candidate risk gene in different populations. In addition, we also evaluated candidate risk gene and 22 immune cells correlation studies. Results There was a significant association between the PDE1C rs12538364 T allele and colorectal cancer risk [odds ratio (OR) = 1.57, 95% confidence interval (CI) = 1.30 – 1.90, P = 3.07 × 10–6, PFDR = 0.004]. Mutation of intron region rs1538364 C to T locus reduces promoter activity of PDE1C in DLD1 and HCT116 cell lines (P < 0.05). We identified that PDE1C is significantly down-regulated in colorectal cancer, closely associated with 22 immune cells. Finally, we found that PDE1C could be the biomarker for individual immunotherapy of colorectal cancer. Conclusion According to our findings, PDE1C may be a key factor contributing to colorectal cancer, thus improving individual immunotherapy for the disease. The potential mechanism by which polymorphisms in the calcium signaling pathway genes may participate in the pathogenesis of colorectal cancer through the tumor microenvironment.